Participações estatais minoritárias e desenvolvimento - Godoy, Eduardo do Prado (2020)
The minority stakes held by state entities in private companies, throughout the twentieth century and at the beginning of twenty-first century, have proved to be an important institutional mechanism for promoting development. As an instrument of economic policy, the State has taken advantage of corporate forays into private agents for various public purposes, ranging from the promotion of productive activity to the regulation of interactions arising from the economic phenomenon. Considering the intense and frequent use of this kind of state action in the processes of production, circulation and distribution of wealth, observed not only in Brazil but in several developed countries, including nations that adhere to neoliberal philosophy, and in view of the still scarce national production of specific studies on the subject, the aim here is to make a contribution to the academic debate, focusing the research on the elements that surround the state minority shareholdings. This study initially deals with the hermeneutics and constitutional systematization of the economic order in the light of the multiple vectors contained in the Federal Constitution of 1988, as well as the legitimation of the shareholder mechanism before such order. The inherent legal characteristics of state minority shareholdings and public-private companies, which are understood as private companies that present the State as a qualified minority partner, is addressed. The study analyses the state minority shareholdings in the international environment, more specifically in France, Germany, the United States and Japan and finally approach the national scenario, being examined the normative overview, the current sectoral distribution of minority stakes held by Brazilian state-owned enterprises and the position of the Federal Court of Auditors on the subject.